Характеристика дефектных частиц вирусной природы у бактерий рода Erwinia - Товкач, Ф.И.; Иваница, Т.В.; Кушкина, А.И. (Видавничий дім "Академперіодика" НАН України, 2008)
For the first time, it is shown that the expression products of defective prophages are typical not only of the defective lysogenic systems of phytopathogenic Erwinia carotovora, but also of epiphytic bacterium Pantoea agglomerans. It is established that viral particles like phage’s capsids are packing a bacterial DNA, whose size is determined by the pulse field gel electrophoresis separation. Based on the data on capsid structures that form the virulent mutant ZF40/421, a proposition about the forming mechanism of defective virions of E. carotovora is made.